A Context-Aware CEO Problem - Seo, Daewon; Lim, Sung Hoon; Kim, Yongjune (IEEE transactions on communications, 2023)
In many sensor network applications, a fusion center often has additional valuable information, such as context data, which cannot be obtained directly from the sensors. Motivated by this, we study a generalized CEO problem where a CEO has access to context information. The main contribution of this work is twofold. Firstly, we characterize the asymptotically optimal error exponent per rate as the number of sensors and sum rate grow without bound. The proof extends the Berger-Tung coding scheme and the converse argument by Berger et al. (1996) taking into account context information. The resulting expression includes the minimum Chernoff divergence over context information. Secondly, assuming that the sizes of the source and context alphabets are respectively |\mathcal {X}| and |\mathcal {S}| , we prove that it is asymptotically optimal to partition all sensors into at most \binom {|\mathcal {X}|}{2} |\mathcal {S}| groups and have the sensors in each group adopt the same encoding scheme. Our problem subsumes the original CEO problem by Berger et al. (1996) as a special case if there is only one letter for context information; in this case, our result tightens its required number of groups from \binom {|\mathcal {X}|}{2}+2 to \binom {|\mathcal {X}|}{2} . We also numerically demonstrate the effect of context information for a simple Gaussian scenario.